Combined dietary administration of Chlorella fusca and ethanol-inactivated Vibrio proteolyticus modulates intestinal microbiota and gene expression in Chelon labrosus - García-Márquez, Jorge; Álvarez-Torres, Daniel; Cerezo Ortega, Isabel M.; Domínguez-Maqueda, Marta; López-Figueroa, Félix; Alarcón, Francisco Javier; Acién-Fernández, Francisco Gabriel; Martínez-Manzanares, Eduardo; Abdala-Díaz, Roberto Teófilo; Béjar-Alvarado, Julia; Arijo-Andrade, Salvador (MDPI, 2023)
The use of functional feeds in aquaculture is currently increasing. This study aimed to assess the combined impact of dietary green microalgae Chlorella fusca and ethanol-inactivated Vibrio proteolyticus DCF12.2 (CVP diet) on thick-lipped grey mullet (Chelon labrosus) juvenile fish. The effects on intestinal microbiota and the transcription of genes related to metabolism, stress, and the immune system were investigated after 90 days of feeding. Additionally, the fish were challenged with Aeromonas hydrophila and polyinosinic–polycytidylic acid (poly I:C) to evaluate the immune response. Microbiota analysis revealed no significant differences in alpha and beta diversity between the anterior and posterior intestinal sections of fish fed the control (CT) and CVP diets. The dominant genera varied between the groups; Pseudomonas and Brevinema were most abundant in the CVP group, whereas Brevinema, Cetobacterium, and Pseudomonas were predominant in the CT group. However, microbial functionality remained unaltered. Gene expression analysis indicated notable changes in hif3α, mhcII, abcb1, mx, and tnfα genes in different fish organs on the CVP diet. In the head kidney, gene expression variations were observed following challenges with A. hydrophila or poly I:C, with higher peak values seen in fish injected with poly I:C. Moreover, c3 mRNA levels were significantly up-regulated in the CVP group 72 h post-A. hydrophila challenge. To conclude, incorporating C. fusca with V. proteolyticus in C. labrosus diet affected the microbial species composition in the intestine while preserving its functionality. In terms of gene expression, the combined diet effectively regulated the transcription of stress and immune-related genes, suggesting potential enhancement of fish resistance against stress and infections.
Keywords: Peces - Alimentación; Algas (Alimento); Acuicultura; Aeromonas hydrophila; Aquaculture; Functional feed; Immune response; Microalgae; Mugilidae; Poly I:C; Probiotic; Stress